The Display of the Process of Becoming a Personality in the Novel “Demian” by Hermann Hesse - SIMYAN, TIGRAN (Bulletin of Yerevan University B: Philology, 2021)
The article discusses the issue of formation of the main character, Emil Sinclair, in the context of other central characters of thenovel (Cromer, Demian, Pistorius, Eva, etc.). The main preconditions for the emergence of personality are Sinclair’s passing through sin, the “Cain’s seal” or the knowledge of his “shadow” (in the Jungian sense), competitiveness, the decoding of non-verbal communicative signs. The emergence of personality in the novel is also presented in the context of Gnosticism and Jungian analytical psychology. The author of the novel offers a concept of transition from opposition and confrontation to synthesis and compromise as one of the main cognitive skills for the formation of personality. This conception suggested by Hesse was used not only for describing the personality of Emil Sinclair, but also for constructing the poetics of the novel as well as all its main characters.
Keywords: socialization, spiritual formation, Identity, self, self-recognition, Gnosticism, Jungian psychology, mythopoetics, myth